A Concept Development of `Being Sensitive' in Nursing - Sayers, Kirstine Lisa (Nursing ethics, 2008)
`Being sensitive' in nursing was explored using Schwartz-Barcott and Kim's hybrid model of concept development, producing a tentative definition of the concept. Three phases were employed: theoretical, empirical/fieldwork and analytical. An exploration of the literature identified where the common idea of `being sensitive' as a nurse was embedded and demonstrated that a theoretical development of this fundamental aspect of nursing was absent. The empirical phase was conducted using semistructured interviews with nine expert palliative care and cancer nurses. This method was particularly useful for the exploration of this concept because of its firm grounding in practical example. A definition of what the concept `being sensitive' means in nursing, and subsequent clarification of `being insensitive', have been posed from the research process undertaken. The essential nature of this concept being integral to nursing practice is emphasized. Potential implications for the development of nursing practice through teaching of this concept were identified.